TINJAUAN PENDAFTARAN TANAH TERHADAP ALAT BUKTI SERTIFIKAT YANG DIAKIBATKAN PUTUSAN PENGADILAN DI KANTOR PERTANAHAN KOTA SURAKARTA - KUMALASARI, ENDAH FITRI (Dinamika Hukum, 2017)
This research aims to study and analyze the influence of court decision on the cancel of certificate (case of supreme court number 645K/TUN/2015) and the implementation of land regristation in land office in realizing law certainty in order that can be accounted for law. Background. Dealing with land lawwhich often arise on society, there is land dispute, start from one of parts because of reluctance and demands toward the land rights about the land status, priority, the owner with the purpose has certainty of administrative, along with law. Research method. The locatison is on minstry agraria office, spatial room, and land agency of surakarta. This research use normative empirical. This character of research is descriptive. Research object is the certificate cancelling implementation on court decision in Land office Surakarta. The data which is observed is secundary data formed written document that supported by primary data as complement, got dirrectly from its source. In this research, the obtained data is from parties related with certificate applicant ownership right and the agraria holder (land office of Surakarta) Conclusion, decision of Indonesia supreme court nomber 645 K/TUN/2015 that the cassation application proposed to Head Office of Land (Cq. SUYADI H) has been determined that cassation application by H. SUYADI/ head of land office rejected. This based on the decision of Judex Facti has been true and there is no legal error. Thus, the decicion of administratin court decision in dispute land, so court of appeal decide the same as comparation court, that is freehold title nomber 4648, Kelurahan Pajang, Kecamatan Laweyan, Surakarta Cit, Jawa Tengah Province, published on 10 september 2001, letter of measurement: 872/pajang/2001 date of 25-5-2001, SUBARNO, transfrom the right becomes SUYADI H. On 24 October 2013. The proposal from 2016 numbered 155 and from january till june numbered 78 from the the change of certificate applicant which propose to Land Office in proposal reality to do substitution publishing. This is including giving service of substitution certificate in the case of certificate cancelling (case of Supreme Court decision No 645 K/TUN/2015) Key word: court decision and substitution certificate